Be on the Lookout for Bacterial Leaf Streak of Corn - K. A. Korus; N. S. Dufault (EDIS)
Bacterial leaf streak (BLS) is a new corn disease that has been found in several of the United States’ major corn producing regions (Korus et al., 2017).  Florida growers should be on the lookout for BLS as it is spreading quickly across the U.S.  Early detection is critical to mitigate the potential damage from this disease and keep Florida’s corn production safe.